Comparative assessment of various supplementary diets on commercial honey bee (Apis mellifera) health and colony performance. - Saboor Ahmad (Public Library of Science (PLoS), 2021)
A healthy honey bee stock is critical to the beekeeping industry and the sustainability of the ecosystem. The quality of the supplemental diet influences the development and strength of the colony, especially during the pollen dearth period in the surrounding environment. However, the extent to which pollen substitute protein feeding affects honey bee colony parameters is not fully known. We conducted this study to test the influence of various supplemental diets on foraging effort, pollen load, capped brood area, population density, and honey yield. The treatment groups were supplied with patties of pollen substitute diets, whereas sugar syrup was given to the control group. Our results indicated that honey bees consumed a significantly higher amount of Diet 1 (45 g soybean flour + 15 g Brewer's yeast + 75 g powdered sugar + 7.5 g skimmed milk + 7.5 g date palm pollen + 200 mL sugar syrup supplement with Vitamin C) followed by others supplemented diets. Further, pollen load, worker-sealed brood area, population strength, and honey yield differed significantly when Diet 1 was consumed instead of other supplemental diets. The proportion of biological parameters was less in the control group as compared to other treatments. This study highlights the potential of supplemental diets to improve the bee's health and colony development when the pollens availability and diversity are insufficient.